PENCATATAN PERKAWINAN : ANTARA RUKUN NIKAH DAN SYARAT ADMINISTRATIF - Arif Marsal (UIN SUSKA RIAU, 2015)
The compilation of Islamic law approved for use by Presidential instruction number 1 of 1991 articles 4, 5, 6, 7 discuss about marriage’s record keeping. Article 4 of it clarifies that the validity of the marriage can only be done in according to Islamic law. Article 5, however, explains that Muslim has to write up their marriage for the sake of the orderliness and the implementation of it has to be done according to the law number 22 of 1946 jo law number 32 of 1954. Article 6, on the other hand, says that marriage has to be done in front of the marriage written official, and if it has not yet been done so, that marriage has no law sturdy. Article 7 explains about marriage can only be evidenced by marriage certificate, if it does not have it yet, they may make marriage itsbat.